Analisis Environmental Kuznets Curve (Menyeimbangkan Industri Hijau dan Degradasi Lingkungan di Indonesia) - M. Zul Mazwan; Anas Tain (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Indonesia has expanded and adapted to international market trends in tandem with the advancement of its industry. Various factors, such as industrialization, urbanization, and the exploitation of natural resources, are responsible for this growth. However, these activities have also led to environmental degradation in many parts of Indonesia. Deforestation is one of the most significant environmental issues that Indonesia is currently grappling with. The production structure of developing countries can exacerbate the relationship between environmental degradation and economic growth, which can be detrimental to the environment. The primary objective of this study is to examine the relationship between environmental degradation and green economic growth, with a particular emphasis on Gross Domestic Product (GDP), using the Environmental Kuznets Curve (EKC) model. This model posits a reversible relationship between per capita income and environmental quality. The novelty of this study lies in the development of better indicators to measure EKC and Green GDP. These indicators cover a wide range of aspects, from air and water quality, and biodiversity levels, to energy consumption. The Pearson correlation analysis was employed to examine the correlation between GDP and IKLH in Indonesia from 2010 to 2022. The analysis yielded positive and robust correlations between GDP and IKLH. Consequently, the higher the GDP, the greater the IKLL or the less environmental degradation. An advance in the economy during the industrial era in Indonesia is indicated by the increase in the country's GDP growth rate. The short-term and long-term impact of economic expansion on the environmental quality index of life suggests that there is a reduction in environmental degradation. The concept of Green GDP should be proposed as an alternative indicator that considers asset depreciation, non-market economy, and environmental damage caused by economic growth.